The effect of compression garments (SKINs) on ventilation and blood lactate after exhaustive exercise - Lambert, S.; Duffy, B.; Chow, C. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
Compression garments have been extensively used for deep venous thrombosis prevention. In-house studies of SKINs compression garments have shown reduced blood lactate levels after exercise. It is hypothesised that SKINs reduce muscle intra-cellular hydrogen ion concentration by increasing oxygen availability to muscle cells. 21 male elite rugby league players performed two treadmill tests to exhaustion within 45 minutes of each other. The first of these tests involved increases in slope every minute until exhaustion. The second test repeated the maximum work level achieved and continued until exhaustion. Expired gas was measured throughout this test. Subjects were randomly allocated to wear skins (tops and shorts; n=10) or no skins (n=11). There were significant differences between blood lactate 15 minutes post-exercise, VEmax and time to exhaustion but not between blood lactate 3 minutes post exercise or VO2max. Skins No Skins Significance Peak Blood Lactate - 3 minute (mmol.l-1) 13.9 +/- 2.75 14.8 +/- 1.75 NS p=0.3774 Blood Lactate - 15 minute (mmol.l-1) 7.0 +/- 2.45 9.43 +/- 2.98 S p=0.05 VO2 max (Ml.min-1.kg-1) 52.1 +/- 4.32 52.6 +/- 5.95 NS p= 0.5221 VE max (L.min-1) 120.9 +/-12.5 110.1 +/- 11.1 S p= 0.0451 Time to exhaustion (seconds) 170.7 +/- 38.6 136.6 +/- 30.1 S p= 0.0351 For the same peak lactate and VO2max, subjects wearing skins had significant improvements in time to exhaustion. Recovery is also accelerated as indicated by significantly lower lactate levels 15 minutes postexercise. The use of upper and lower body compression garments clearly improves exercise tolerance and lactic recovery.